2020
DOI: 10.20473/pmnj.v6i2.19943
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Mothers' Breastfeeding Pattern and Stunting among Toddlers

Abstract: Introduction: Stunting is a condition of the measured height of toddlers, which is less to the age. Stunting, which occurs in these children, is also considered in chronic nutrition problems. The study aimed to discover the correlation between breastfeeding mothers' pattern in breastfeeding for toddlers aged 0 days to 6 months with the stunting incidence in toddlers in Gandatapa village, Sumbang sub-district, Banyumas district.Methods: This study implemented an observational analytic method that examined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
2
1
1
Order By: Relevance
“…This result differs from Azzeh [16] , who reported that nearly three-quarters of the studied sample initiated breastfeeding for their infants within the first 24 hours. Also, this result contradicted those obtained by Firdausya & Hardini [17] who studied ''the correlation between mothers' breastfeeding pattern and stunting among toddlers'' and reported that the majority of the studied mothers who had normal babies starting breastfeeding within hours after delivery. In addition, Azzeh [16] said that half of the studied mothers initiated breastfeeding during the first 24 hours of infants' lives.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This result differs from Azzeh [16] , who reported that nearly three-quarters of the studied sample initiated breastfeeding for their infants within the first 24 hours. Also, this result contradicted those obtained by Firdausya & Hardini [17] who studied ''the correlation between mothers' breastfeeding pattern and stunting among toddlers'' and reported that the majority of the studied mothers who had normal babies starting breastfeeding within hours after delivery. In addition, Azzeh [16] said that half of the studied mothers initiated breastfeeding during the first 24 hours of infants' lives.…”
Section: Discussioncontrasting
confidence: 82%
“…Regarding offering exclusive breastfeeding, the current study showed that three-quarters of the studied mothers offered exclusive breastfeeding to their infants. This result was confirmed by Firdausya & Hardini [17] , who stated that near two-third of the studied mothers offered exclusive breastfeeding to their infants. This result contradicted with findings of Kamel, Sabry, Ismail, & Nasr [18] studied ''Pattern of infants' feeding and weaning in Suez Governorate, Egypt: an exploratory study'' and reported that most infants were ever breastfed.…”
Section: Discussionsupporting
confidence: 81%
“…In line with this research, another study conducted in Gorontalo explained that stunting occurs not due to factors such as exclusive breastfeeding or complementary breastfeeding, but one of them is due to variations in the provision of complementary foods (Nurdin et al, 2019). This is different from other studies which explain that the habitual patterns of mothers in breastfeeding their children such as exclusive breastfeeding and when complementary foods are given are related to the incidence of stunting (Firdausya & Hardini, 2020) (Larson et al, 2019).…”
Section: The Behavior Of Giving Asi/mpasi Mothers To Their Childrenmentioning
confidence: 58%
“…A study by Semahegn et al showed that mothers who started breastfeeding before the age of 6 months were caused by a lack of mother's knowledge (Agumasie Semahegn, Gezahegn Tesfaye, 2014). Generally, in the family, the person who plays an important role in decision-making for IYCF practices is the mother (Cunningham et al, 2021), but it turns out that a study by Firdausya and Hardini found that some grandmothers told the mothers to give food to their babies when they were under six months old (Firdausya & Hardini, 2020). However, this study showed that mothers who have good IYCF knowledge and attitude towards appropriate IYCF practices have not been successful in implementing IYCF practices according to recommendations because neither caregivers nor grandmothers do not necessarily have the same positive knowledge and attitudes as well as mothers.…”
Section: Discussionmentioning
confidence: 99%